ANALISA PENGARUH VARIASI KUAT ARUS PENGELASAN FLUX CORED ARC WELDING (FCAW) TERHADAP SIFAT KEKERASAN PADA DAERAH HAZ BAJA KARBON RENDAH - Huka, Graciadiana. I.; Matheus, Josef; Nanulaitta, Nevada JM.; Pattikayhatu, Erwin Bravor (Journal Mechanical Engineering, 2024)
Welding is a process of joining metals by utilizing electric power as a source of welding heat. Flux-Core Arc Welding (FCAW) is a welding process that uses a heat source from electricity that is converted into a heat source in an electric arc, in this FCAW welding the type of protection used is flux or powder that is in the core of the welding wire (the welding wire is rolled in a roll). This research aims to observe changes in hardness values after welding, both low carbon steel hardness in the HAZ (Heat Affected Zone) area and outside the HAZ (Heat Affected Zone) area. Welding using V-joints with angles of 45° and 60° and varying the voltage strength at 16 volts, 18 volts and 20 volts. Hardness testing using the Rockwell method where the highest hardness value of the HAZ area for 45 is 22.95 HRD at a voltage strength of 20 volts. For V-joints for an angle of 60°, the highest hardness value of the HAZ area is also at a voltage strength of 20 volts with a value of 24.10 HRD. The highest increase in hardness value is at the V-angle 60° joint with a voltage of 20 volts with a hardness value of 21 HRD while the lowest is the V-angle 45° joint with a voltage of 16 volts at 18.67 HRD. Keywords: Hardness Value, HAZ (Heat Affected Zone), FCAW (Flux Cored Arc Welding)